Evaluation of Reference Genes for Real-Time Quantitative PCR Analysis in Larvae of Spodoptera litura Exposed to Azadirachtin Stress Conditions - Shu, Benshui; Zhang, Jingjing; Cui, Gaofeng; Sun, Ranran; Sethuraman, Veeran; Yi, Xin; Zhong, Guohua (Frontiers in Physiology, 2018)
Azadirachtin is an efficient and broad-spectrum botanical insecticide against more than 150 kinds of agricultural pests with the effects of mortality, antifeedant and growth regulation. Real-time quantitative polymerase chain reaction (RT-qPCR) could be one of the powerful tools to analyze the gene expression level and investigate the mechanism of azadirachtin at transcriptional level, however, the ideal reference genes are needed to normalize the expression profiling of target genes. In this present study, the fragments of eight candidate reference genes were cloned and identified from the pest Spodoptera litura. In addition, the expression stability of these genes were evaluated by the computational methods of NormFinder, BestKeeper, Delta CT, geNorm and RefFinder in different samples from larvae of control and azadirachtin treatments. According to our results, two of the reference genes should be the optimal number for RT-qPCR analysis. Furthermore, the best reference genes for different samples were showed as followed: EF-1α and EF2 for cuticle, β-Tubulin and RPL7A for fat body, EF2 and Actin for midgut, EF2 and RPL13A for larva and RPL13A and RPL7A for all the samples. Our results established a reliable normalization for RT-qPCR experiments in S. litura and ensure the data more accurate for the mechanism analysis of azadirachtin.